The role of the teacher-nurse in health education - Valdez, Fermina Antiga (1972)
The qualifications and functions of teacher-nurses in the Bureau of Public Schools and their implications for health education was sought for study in this paper. On the basis of biographical data obtained and presented in this paper, it was concluded that there is a need for professionally trained teacher-nurses who are equipped with the understanding, attitudes, skills and knowledge necessary to fulfill their obligations effectively to school children and to the community. From the list of their functions, there is obviously a need for preparation. It was recommended that the recruitment and selection of teacher-nurses be based on training and merit system and should meet certain criteria.